You are on page 1of 3

# 2004 Mathematics Extension 2, 1990 Syllabus

Topic 4: Integration

Using the Reverse Chain Rule du u dx dx = u du , the objective is to have u and its derivative sin x e tan x dx Examples: dx , let u = tan x ; tan xdx = 2 cos x cos x ex We also look for similarity to the standard integrals: dx , let u = e x 2x 1+ e 1 dx x Also pay attention to the natural domain: x ln x = ln x dx = ln( ln x ) + c = dx The domain of includes 0 < x < 1 and so allows the ln x to be negative. Hence x ln x the integral ln ( ln x ) + c must be written as ln ln x + c . Sometimes the || is not necessary because there never will be negative values to be ln-ed. Remember that || actually means modulus (in case the thing inside is a complex number). Reminder: for indefinite integrals, dont forget to convert u back to its x expression. Algebraic Manipulation to Reduce Fractional Integrand to Standard Form x + 1 Expand and simplify: dx = x + 2 + 1 dx ; dx x x x Note: (1) each term in numerator is divided by denominator; (2) coefficients 3x 1 3x 1 3 2x 1 dx = 2 2 dx = 2 dx can be manipulated: 2 2 2 x +1 x +1 x +1 x +1 x +1 Rewrite as partial fractions: this will often result in a series of ln functions, so revise the log rules to combine them into one. Some special cases: 3 ( 2 x + 1) 7 3x 2 2 dx = 3 7 1 dx Both functions linear: dx = 2 2 2 2x + 1 2x + 1 2x + 1 2 2 x x +1 1 1 dx = dx = 1 2 dx Not linear but can be rewritten: 2 2 x +1 x +1 x + 1 Denominator is an irreducible quadratic ( < 0 ) or a quadratic in a square root, numerator is linear or constant: complete the square of the quadratic, then you may need to substitute u = (the thing in brackets) [if the quadratic is reducible, use partial fraction]; Example: 2x + 1 2x + 1 x 2 + 2 x + 2 dx = ( x + 1) 2 + 1 dx , let u = x + 1 Using More Sophisticated Substitution to Reduce the Integrand 1 dx, let u = x ; Algebraic substitutions, often of squares: ( 4 + x) x x +1

x +1 Trigonometric substitutions x = a sin , a sec or a tan : especially when the integrand contains a 2 x 2 , x 2 a 2 or even a 2 + x 2 [a can be 1] but is not in the table of standard integrals; then use Pythagorean identity to write it differently [Theres a restriction on the values of , as implied by the inverse trig functions.] [The primitive may have sin 1 x + c part; this is the same as cos 1 x + d .]
2

x3

## dx, let u = x 2 + 1 or u 2 = x 2 + 1 (then do implicit differentiation)

Page 1 of 3

http://www.geocities.com/nsweducationalservice

## 2004 Mathematics Extension 2, 1990 Syllabus

Topic 4: Integration

An example illustrating algebraic manipulation OR trigonometric substitution [with xn x 2 + 1 x n 2 x n 2 recurrence formula]: I = 2 dx : let x = tan OR write as dx x +1 x2 +1

Integration of Trigonometric Functions Rewrite the integrand so it can be easily integrated (for example, its in the table of standard integrals or it has u and its derivative). Do this by trigonometric identities. m m m Integrals of the form sin d OR cos d [OR sin a d etc.], m +ve even
2 2 etc. and sin = 1 2 (1 cos 2 ) ; cos = 1 2 (1 + cos 2 ) m m m Integrals of the form sin d OR cos d [OR sin a d etc.], m +ve odd Use Pythagorean identity and substitution, for example: 3 2 2 2 cos d = cos cos d = 1 sin cos d = 1 u du , u = sin x

## Write sin m as sin 2

Pythagorean identities: sin 2 + cos 2 = 1 , etc. [dividing sin 2 + cos 2 = 1 by cos 2 gives tan 2 + 1 = sec 2 ] m n Integrals of the form sin cos d , where at least one of m and n is +ve odd integral as sin m cos n 1 cos d = sin m 1 sin 2

Suppose n is odd [so n 1 is even]. Note that the derivative of sin is cos. Rewrite the

n 1 2

cos d .

## Integrals of the form sin m cos n d , cos m cos n d , sin m sin n d

2 sin p cos q = sin ( p q ) + sin ( p + q ) , Use product to sum formulae: 2 cos p cos q = cos( p q ) + cos( p + q ) , 2 sin p sin q = cos( p q ) cos( p + q ) . Perhaps its enough knowing any 1 formula because we can use the identity sin 2 x = cos x . The substitution t = tan x 2 : will convert trigonometric functions into an algebraic 1 2t 1 t2 2t dx ; sin x = function, used e.g. in , cos x = , tan x = 2 2 1 + sin x 1+ t 1+ t 1 t2

Integration by Parts dv du Formula: u dx = u v v dx dx dx In words: int. of existing parts = parts without dx int. of the new parts We want the new parts to be easily integrated. This is generally done by: choosing dv/dx as the function which can be integrated, and often without raising the power; choosing u as the function which can be easily differentiated, and hopefully looks simpler after its differentiated. Some functions, such as e and sin, display a nice pattern when differentiated or integrated. If your choice doesnt work, you can usually swap them. LIATE (Log, Inverse trig, Algebra, Trig, Exponential): is a useful acronym for determining which part should be u and which should be dv/dx. The function whose letter 1 comes first in LIATE is u. Example: x sin xdx , x is algebra so its dv/dx. Sometimes we need to introduce 1. Example: ln x dx = 1 ln x dx ; u = ln x . Sometimes integration by parts must be carried out more than once, the second of which x brings us back to the original integral. Example: let I = e sin x dx = = e x cos x I ; moving I to LHS gives 2 I = e x cos x . You may need to use simple substitutions to find out the integral of the new parts. Page 2 of 3

http://www.geocities.com/nsweducationalservice

## 2004 Mathematics Extension 2, 1990 Syllabus Note on Definite Integral k k du k dv u dx = uv v dx c dx c c dx

Topic 4: Integration

Recurrence or Reduction Formula Sometimes the integral is so naughty that the integral of the new parts looks similar to the original integral, except that it has a different power. The notation I n is used to denote the original integral with power n, I n 1 denotes the same integral but with power n 1 , etc. A question usually gives the formula which you have to show. n x n x Application: suppose we have shown that I n = x e dx = x e nI n 1 , find I 3 . I 3 = x 3 e x 3I 2 = x 3 e x 3 x 2 e x 2 I 1 = x 3 3 x 2 e x + 6 I 1 = x 3 3 x 2 e x + 6 xe x 1I 0

) (

## But we can find I 0 , which is

Definite Integral: we can let I n = f ( x ) dx . A nice thing with this is that the recurrence
k c n formula wont contain any x. Example: show I n = 0 x 1 x dx = 1

x e
0

dx = e x + C .

6 64 642 2 I2 = I1 = I 0 , and I 0 = . 9 97 975 3 We can also find expression for I n in factorial notation (without recurrence relation). n!( n + 1)! n +1 4 Example: referring to the previous question, show that I n = ( 2n + 3)! . To do this, 2n 2n 2n 2 2n 4 6 4 2 2 I n 1 = = ( i.e. I 0 ) then proceed spell out I n = 2n + 3 2 n + 3 2 n + 1 2n 1 9 7 5 3 with your skills I3 =

2n I n 1 ; find I 3 . 2n + 3

Recurrence Formula Involving Single Trigonometric Function Raised to a Power n 1 I n 2 . Convert this expression into Example: I n = 2 cos n xdx . Show that I n = 0 n factorial notations. n 1 dv I n = 2 cos n xdx = 2 cos x cos n 1 xdx , we choose u = cos x, dx = cos x because 0 0 theres I n 2 in the question so we want cos n 2 in the new parts. n 1 I n 2 relates I n to I n 2 , we need to consider separate Because the expression I n = n cases for odd and even n when finding the factorial notations. Further Properties of Definite Integrals Assumption:
b

## f ( x ) dx = f ( u ) du [proof: kinda common sense]

b a 2

x2 2 e x + 1 dx using the substitution u = x . It is also used to prove the following theorems. This idea can be used, for example, to evaluate
a

## Theorem #1: Theorem #2:

a a

f ( x )dx =
a 0

{ f ( x ) + f ( x )}dx

[proof: let u = x ]

f ( x )dx
0

= f ( a x )dx

[proof: u = a x ]

I think questions should hint you if you need to use these theorems. Page 3 of 3 http://www.geocities.com/nsweducationalservice